2010
DOI: 10.1007/s10533-010-9494-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic microbial activity in lake sediments: effects of organic electron donors

Abstract: Allochthonous and autochthonous organic matter deposited in benthic sediments are mineralized by microbial communities, resulting in release of nutrients to the water column. Lakes with different trophic states may have sediments with different carbon and nutrient concentration with consequently different microbial communities. Microbial diversity of surface sediments of three subtropical lakes of different trophic state was investigated by measuring catabolic response to a wide variety of carbon-substrates. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 62 publications
1
26
0
2
Order By: Relevance
“…Stratigraphic fluctuations in the d 13 C and d 15 N values of Lake Annie sediment OM probably reflect a combination of factors, including a shift in relative contribution of autochthonous/allochthonous OM, changing autochthonous primary productivity, and relative microbial biomass and activity (Torres et al 2011). Small, oligotrophic lakes might be expected to have relatively high proportions of allochthonous C contribution to sediment OM (Gu et al 1996).…”
Section: Lake Anniementioning
confidence: 99%
See 1 more Smart Citation
“…Stratigraphic fluctuations in the d 13 C and d 15 N values of Lake Annie sediment OM probably reflect a combination of factors, including a shift in relative contribution of autochthonous/allochthonous OM, changing autochthonous primary productivity, and relative microbial biomass and activity (Torres et al 2011). Small, oligotrophic lakes might be expected to have relatively high proportions of allochthonous C contribution to sediment OM (Gu et al 1996).…”
Section: Lake Anniementioning
confidence: 99%
“…Consequently, 13 C-rich CO 2 is transferred from the sediments to the DIC of the water column (Gu et al 2004). Lake Apopka sediments display high CH 4 production rates (Torres et al 2011). Furthermore, most of the OM generated by primary productivity in this lake is deposited in its sediments (Gale and Reddy 1994).…”
Section: Lake Apopkamentioning
confidence: 99%
“…The oligo-mesotrophic lake sediment microorganisms had lowest efficiency in use of energy [1]. The lack of water circulation in stratified water bodies (with a thermocline and halocline) in conjunction with continuous O 2 -consumption by remineralization leads eventually to complete O 2 depletion.…”
Section: Metabolic Patternsmentioning
confidence: 99%
“…Microbial biomass may be significantly in relation to rate of C source consumption in all lake sediments, suggesting that microbial activity is limited by C availability. Findlay (2003) showed that the addition of different carbon sources, i.e., glucose, bovine serum albumin and natural leaf leachate to hyporheic biofilms enhanced microbial activities [1]. Carbon sources may influence nitrate reducing activity of the biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…The linkage between nutrient loading, ecosystem trophic status, and sediment properties is not always direct. For example, Torres et al (2011) examined sediment properties of three lakes of widely varying trophic status, ranging from oligotrophic to hypereutrophic. They found the surface sediment of an oligotrophic lake to have the highest total P (1427 mg P kg −1 ), as well as highest labile forms of P, of the lakes they studied.…”
Section: Soil Depthmentioning
confidence: 99%